2016
DOI: 10.15376/biores.11.4.10575-10584
|View full text |Cite
|
Sign up to set email alerts
|

Fungitoxic Potential of Extracts of Four Pinus spp. Bark to Inhibit Fungus Trametes versicolor (L. ex. Fr.) Pilát

Abstract: Pinus bark was extracted through a mixture of acetone-hexane-water 54:44:2 V. Bioassays were performed according to the agar dilution method (petri dish) using concentrations of 0.1, 0.5, and 1.0 mg mL -1 for each of the obtained extracts. All extracts showed some inhibition degree. Crude extracts of P. strobus bark showed the greatest inhibition degree. Antifungal potential of all tested extracts at a concentration of 1.0 mg mL -1 was classified as toxic. Through simple regression models, concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Lomeli-Ramírez et al [40] reported toxic effects of extracts from P. strobus, P. douglasiana, P. caribea and P. leiophylla toward T. versicolor. Similarly, Maritime pine extracts exhibited a significant antifungal potency against C. puteana and T. versicolor which mycelia growth was reduced by 89% and 87%, respectively [20].…”
Section: Discussionmentioning
confidence: 99%
“…Lomeli-Ramírez et al [40] reported toxic effects of extracts from P. strobus, P. douglasiana, P. caribea and P. leiophylla toward T. versicolor. Similarly, Maritime pine extracts exhibited a significant antifungal potency against C. puteana and T. versicolor which mycelia growth was reduced by 89% and 87%, respectively [20].…”
Section: Discussionmentioning
confidence: 99%